Pembangunan Sistem Informasi Wirausaha Mahasiswa (Siwirma) Berbasis Web - Kaleb Endless Fidel; Muchammad Ardhian Wicaksono; Andi Setiawan (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
Marketplace is a place where sellers and buyers meet online, which has several benefits, including expanding the network and increasing sales, especially for small and independent businesses with medium to low capital. Included in the category of micro, small, and medium enterprises (MSMEs) are businesses carried out by student groups. Students who have no experience in entrepreneurship need to receive direction that they have independent business opportunities, and those who are currently running entrepreneurship need to know the factors that influence entrepreneurial success and train skills for success. Marketing and sales factors are among several important factors that influence entrepreneurial success. Based on this background, the student research team will develop a marketplace information system for student business units both within the Semarang Institute of Technology and Business campus and outside the campus, named the Sistem Informasi Wirausaha Mahasiswa (Siwirma).